2012
DOI: 10.1016/j.chemosphere.2011.11.017
|View full text |Cite
|
Sign up to set email alerts
|

VOC composition of current motor vehicle fuels and vapors, and collinearity analyses for receptor modeling

Abstract: The formulation of motor vehicle fuels can alter the magnitude and composition of evaporative and exhaust emissions occurring throughout the fuel cycle. Information regarding the volatile organic compound (VOC) composition of motor fuels other than gasoline is scarce, especially for bioethanol and bio-diesel blends. This study examines the liquid and vapor (headspace) composition of four contemporary and commercially available fuels: gasoline (<10% ethanol), E85 (85% ethanol and 15% gasoline), ultra-low sulfur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 19 publications
1
32
0
Order By: Relevance
“…A lower R 2 of 0.516 and higher percentage contributions (15% for VOC and 11% for PM 2.5 ) were observed for diesel exhaust, compared to those of natural gas in the original D Comb data set (Table 3, D FCor ). The problem of profile collinearity might be solved by including additional species to reduce similarity between profiles (Chin and Batterman, 2012). These above analyses indicated a trade-off between high and low contributors when they correlated with each other.…”
Section: C2mentioning
confidence: 99%
See 1 more Smart Citation
“…A lower R 2 of 0.516 and higher percentage contributions (15% for VOC and 11% for PM 2.5 ) were observed for diesel exhaust, compared to those of natural gas in the original D Comb data set (Table 3, D FCor ). The problem of profile collinearity might be solved by including additional species to reduce similarity between profiles (Chin and Batterman, 2012). These above analyses indicated a trade-off between high and low contributors when they correlated with each other.…”
Section: C2mentioning
confidence: 99%
“…On the other hand, for the low contributors of coal combustion and natural gas, their R 2 increased to 0.784 and 0.953, respectively, although their percentage contribution estimates also increased. Source profile collinearity was investigated by replacing natural gas in D Comb with diesel exhaust which has a profile highly correlated with that of vehicle exhaust (Chin and Batterman, 2012). A lower R 2 of 0.516 and higher percentage contributions (15% for VOC and 11% for PM 2.5 ) were observed for diesel exhaust, compared to those of natural gas in the original D Comb data set (Table 3, D FCor ).…”
Section: C2mentioning
confidence: 99%
“…However, gasoline compositions in recent literature that have reported similar target species, including n-butane, npentane, 2-methyl butane, toluene, and m,p-xylene (Harley and Kean, 2004;Na et al, 2004;Chin and Batterman, 2012). In a 2006 study of diesel fuel in Taiwan, the top five VOCs were C 13 -C 16 and C 18 straght-chain alkanes, accounting for 46% of target compounds (Peng et al, 2006).…”
Section: Characterization Of Vocs At the Airport Apronmentioning
confidence: 99%
“…In a 2006 study of diesel fuel in Taiwan, the top five VOCs were C 13 -C 16 and C 18 straght-chain alkanes, accounting for 46% of target compounds (Peng et al, 2006). Chin and Batterman (2012) indicated that C 9 -C 16 straightchain alkanes of diesel fuel were dominant and account for 90% of TVOCs. Branched paraffines (29.94%) represent the largest proportion of C 5 -C 9 VOC composition of jet fuels, follow by monocyclic paraffines (20.34%), n-paraffines (19.69%), alkyl benzenes (14.05%), and others (15.98%) (van der Westhuizen et al, 2011).…”
Section: Characterization Of Vocs At the Airport Apronmentioning
confidence: 99%
“…Alkenes are widely emitted from biogenic and anthropogenic sources (Kesselmeier et al, 2002;Chin and Batterman, 2012), and their gas-phase oxidation reactions with OH, NO 3 , or O 3 are among the most important processes in the atmosphere (Atkinson, 1997;Stewart et al, 2013;Paulson et al, 1999). Reactions of ozone with alkenes are an important source of free radicals in the lower atmosphere and thus highly influence the oxidative capacity of the atmosphere (Paulson and Orlando, 1996).…”
Section: Introductionmentioning
confidence: 99%